Creating web pages simplified - Wooldridge, Mike Rao; Stuart, Brianna (Indianapolis, Indiana : John Wiley & Sons, 2011)
In Creating Web Pages Simplified, readers get the building blocks needed to take them through all phases of Web publishing; from laying out and formatting text to enlivening pages with graphics and animation. This full-color, easy-to-follow guide is an indispensable tool for both first-timers and seasoned Web authors
1. Getting started with HTML5 and web pages -- 2. Creating your first HTML5 web page -- 3. Adding and modifying text -- 4. Adding CSS styles --
5. Styling text -- 6. Adding images -- 7. Adding links -- 8. Working with tables -- 9. Creating forms -- 10. Controlling page layout -- 11. Adding semantic tags -- 12. Working with JavaScript -- 13. Adding canvases -- 14. Adding video and audio -- 15. Publishing your web pages
Includes index
Keywords: Web site development; Web site -- Design; Web site -- Desig -- Handbooks, manuals, etc